Acute Gastrointestinal radiation toxicities in pelvic radiation therapy; types, grade and frequency - Ali Rasheed, Hadeel M.; Sabeeh Al-Rawaq, Khudair J. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: quality of life of cancer survivors is adversely impacted by bowel toxicity; result from pelvic radiation therapy. In the UK, 12000 patients are treated with radiation therapy for pelvic cancer, mostly with curative intent; this carries a considerable risk for normal surrounding tissues side effects.Objective: the aim of this study was to determine the frequency, types and grade of acute gastrointestinal toxicity in radical pelvic radiation therapy in our patients so that a comparison could be made with the Western countries.Patients and Methods: a prospective analytic study was carried out in Radiotherapy department / Oncology teaching hospital / Medical city complex, from the 2nd of January to the 30th of April 2016. A total of 53 patients with histologically confirmed uterine, cervical, rectal, urinary bladder or prostatic cancer, treated by radical radiation therapy, were enrolled in the study. Patients were assessed for the frequency, types and grade of acute gastrointestinal toxicities according to grading criteria of CTC (Common Toxicities Criteria), at the start, during and at the end of the treatment. The data was analyzed by the Statistical Package for Social Sciences (SPSS 20).Result: out of 53 patients, 60.37% (32) were female and 39.62% (21) were male. Endometrial cancers represent 30.18% of the cases, cervical cancers were 24.52%, and rectal cancers 11.32%, urinary bladder cancers 24.52% and prostatic cancers were 9.43% of the total cases. Diarrhea was present in 50.9% of the patients; nausea and vomiting were present in 22.6% for each. The majority had grade 1 toxicities and only 2 patients developed grade 3 diarrhea (4.7%).Conclusion: The type and incidence of acute gastrointestinal toxicities in pelvic radiation therapy were mostly related to; Radiation dose, a combined used of chemotherapy with radiation therapy and surgery.